HUBUNGAN PERAN DAN PERILAKU PERAWAT DENGAN PENCEGAHAN DAN PENGENDALIAN INFEKSI DI RSUP DR. SITANALA TANGERANG - Putri Widiana Puspitasari (2023)
Healthcare-associated infections (HAIs) are one of the health problems experienced by almost all countries, including Indonesia. Cross-infection is one of the infections that affect HAIs, nurses are the ones who work in hospitals and interact with patients for 24 hours. The purpose of this study was to determine the relationship between the role and behavior of nurses and the characteristics of respondents with infection prevention and control measures. This research was conducted in June 2023 at Dr. Sitanala Tangerang Hospital. This research method uses quantitative with a Cross-Sectional approach. Sampling is total sampling of 100 respondents. The results of the Chi-Square test obtained a p value <0.05 (0.006) meaning that there is a relationship between the role of and infection prevention and control measures. Chi-Square Test Results P value <0.05 (0.009) means that there is a relationship between behavior in terms of nurses' actions and infection prevention and control. The recommendation from this study is the need for action from hospital management to improve the quality of nurses by providing training or support for infection prevention and control measures in order to maximize PPI measures.